2015
DOI: 10.1080/15592324.2015.1082697
|View full text |Cite
|
Sign up to set email alerts
|

Circadian changes in endogenous concentrations of indole-3-acetic acid, melatonin, serotonin, abscisic acid and jasmonic acid in Characeae (Chara australis Brown)

Abstract: Giant-celled Characeae (Chara australis Brown), grown for 4 months on 12/12 hr day/night cycle and summer/autumn temperatures, exhibited distinct concentration maxima in auxin (indole-3-acetic acid; IAA), melatonin and serotonin about 4 hr after subjective daybreak. These concentration peaks persisted after 3 day pretreatment in continuous darkness: confirming a circadian rhythm, rather than a response to "light on." The plants pretreated for 3 d in continuous light exhibited several large IAA concentration ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 73 publications
(92 reference statements)
1
38
0
Order By: Relevance
“…Nevertheless, MEL content has been found to vary in some species of plant seasonally and also on a daily basis suggesting that even if it is not a primary chronoregulator in plants, it plays a role in timing both chronoregulatory processes and reproductive development 36,44 . Additionally in several cases, this rhythm was maintained even when plants were kept in the dark, confirming endogenous maintenance of this system 117,118 . One possibility is that the MEL content is synchronized, with photosynthetic activity with daylight as the photosynthetic process producing large quantities of dangerous free radicals and reactive oxygen species 4,43,119,120 .…”
Section: Melatonin and 5ht In Flowering Reproduction And Chronoregulmentioning
confidence: 53%
“…Nevertheless, MEL content has been found to vary in some species of plant seasonally and also on a daily basis suggesting that even if it is not a primary chronoregulator in plants, it plays a role in timing both chronoregulatory processes and reproductive development 36,44 . Additionally in several cases, this rhythm was maintained even when plants were kept in the dark, confirming endogenous maintenance of this system 117,118 . One possibility is that the MEL content is synchronized, with photosynthetic activity with daylight as the photosynthetic process producing large quantities of dangerous free radicals and reactive oxygen species 4,43,119,120 .…”
Section: Melatonin and 5ht In Flowering Reproduction And Chronoregulmentioning
confidence: 53%
“…Melatonin is reported to be a molecule having an auxinic activity, where it promotes and inhibits vegetative growth in a similar fashion to IAA (Hernández-Ruiz et al, 2005). Moreover, synchronous circadian concentration changes (double peaks in a 24-h duration) in melatonin, serotonin, and IAA, all of which are produced from the same precursor, tryptophan, are reported in the family Characeae, indicating a possible crosstalk between IAA and melatonin biosynthesis pathways (Beilby et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[94,111-114]]; yet we are only beginning to understand the function of these phytohormones in streptophyte algae [115-117]. All three canonical plant defense phytohormones, JA, SA and ET, have been detected in at least some species of streptophyte algae [94,112,115,118]. They also have been explored with regard to pathogen defense in non-flowering land plants.…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%
“…However, actual (mainly mass spectrometry-based) measurements of JA levels are suggestive of a patchier distribution among land plants and streptophyte algae. For example, while JA is reported to be produced in small quantities in the streptophyte algae K. nitens [94] and Chara australis [118], Hackenberg and Pandey [126] did not detect JA in Chara braunii . Furthermore, Gachet et al [127] did not detect JA in Chara vulgaris and Klebsormidium elegans , while Koeduka et al [128] found only minimal levels of JA in Klebsormidium flaccidum .…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%